2014
DOI: 10.1016/j.canlet.2014.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer stem cells: Multiple capacities in tumor metastasis

Abstract: Breast cancer is the leading cause of cancer death among women worldwide. Accumulating evidence indicates that the local recurrent and/or distant metastatic tumors, the major causes of lethality in the clinic, are related to the aggressive phenotype of a small fraction of cancer cells loosely termed as cancer stem cells (CSCs), tumor initiating cells (TICs), or cancer metastasis-initiating cells (CMICs). Breast cancer stem cells (BCSCs) are shown to exhibit unique growth abilities including self-renewal, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
129
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 98 publications
2
129
1
3
Order By: Relevance
“…8 Consequently there is an urgent need, not only to further define the nature of heterogeneity in breast tumors, but also to develop new therapeutic protocols for targeting this sub-population of "hard core" cancer cells. HSP90 has been considered as an attractive molecular target for cancer therapy for more than a decade, because it can simultaneously affect numerous oncogenic proteins and pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Consequently there is an urgent need, not only to further define the nature of heterogeneity in breast tumors, but also to develop new therapeutic protocols for targeting this sub-population of "hard core" cancer cells. HSP90 has been considered as an attractive molecular target for cancer therapy for more than a decade, because it can simultaneously affect numerous oncogenic proteins and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid confusion with normal stem cells, it has been proposed that cancer stem cells be designated as "tumor initiating cells," or "cancer stem-like cells," thereby defining the subset of cancer cells that has the ability to drive the growth and spread of a tumor. 8 Breast cancer is a significant cause of mortality in women, and has a high incidence of recurrence and treatment failure. It is a heterogeneous disease reflected both at morphological and genetic levels.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem/progenitor cells (CSCs) are a subpopulation of cancer cells with the characteristics of tumor initiation (1), resistance to therapy (2) and metastasis (3). In breast cancer, breast CSCs (BCSCs) have been identified as cells with cluster of differentiation (CD) 24 -CD44 + surface markers (4) or with high intracellular aldehyde dehydrogenase activity (5).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is considered to be the leading cause of cancer-related death among women all over the world [1]. It was reported that approximately 1.38 million people developed breast cancer in 2008; among all cancers, it was ranked second for morbidity, with 23% of all cancer cases, and its mortality was the fifth highest of all cancers [2].…”
Section: Introductionmentioning
confidence: 99%